Climate Change and Agriculture: Adaptation Strategies and Mitigation Opportunities for Food Security in South Asia and Latin America - Jat, Mangi Lal; Dagar, Jagdish Chander; Sapkota, Tek Bahadur; Singh, Yadvinder P.; Govaerts, Bram; López Ridaura, Santiago; Saharawat, Yashpal S.; Sharma, Ramesh Kumar; Tetarwal, J.P.; Jat, Raj K.; Hobbs, Huntington; Stirling, Clare M. (Elsevier, 2016)
During the past two centuries, the world has witnessed a remarkable increase in the atmospheric concentrations of the greenhouse gases (GHGs), namely carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), as a result of human activities after 1750 (preindustrial era). During 1750 the concentrations for these gases were 280 ppm, 715 ppb, and 270 ppb, respectively which increased to 379 ppm, 1774 ppb, and 319 ppb, respectively in 2005. It showed an increase of 0.23, 0.96, and 0.12% annually. The same has further increased to 385 ppm, 1797 ppb, and 322 ppb, respectively in 2008 representing 1.6, 1.2, and 0.9% increase, respectively from 2005 levels at an annual increase of 0.53, 0.43, and 0.31%, annually. Increase in atmospheric CO2 promotes growth and productivity of plants with C3 photosynthetic pathway but the increase in temperature, on the other hand, can reduce crop duration, increase crop respiration rates, affect the survival and distribution of pest populations, and may hasten nutrient mineralization in soils, decrease fertilizer-use efficiency, and increase evapotranspiration. The water resources which are already scarce may come under enhanced stress. Thus, the impact of climate change is likely to have a significant influence on agriculture and eventually on the food security and livelihoods of large sections of the urban and rural populations globally. The developing countries, particularly in South Asia and Latin America, with diverse agroclimatic regions, challenging geographies, growing economies, diverse agricultural production systems, and farm typologies are more vulnerable to the effect of climate change due to heavy dependence on agriculture for livelihood. These regions also are demonstrating poor coping mechanisms to adapt to these challenges, and as a result there is evidence of negative impacts on productivity of wheat, rice, and other crops to varying extent depending on agroecologies. Upscaling of modern technologies such as conservation and climate smart agriculture, judicious utilization of available water for agriculture through microirrigation and water saving technologies, developing multiple stress-tolerant crop cultivars and biotypes through biotechnological tools, restoration of degraded soils and waters, promoting carbon sequestration through alternate production technologies and land use, and conservation of biodiversity must be promoted at regional and country level to ensure durable food and nutritional security. Reliable early warning system of environmental changes, their spatial and temporal magnitude, coupled with policies to support the diffusion of this information, can help interpret these forecasts in terms of their agronomic and economic implications for the benefit of farmers and to provide agriculture-dependent industries and policymakers with more informed options to support farmers. These countries need to formulate both short-term and long-term policies for improvement, sustenance, and protection of natural resources. There is an urgent need for capacity building through international collaboration in order to develop databases and analysis systems for efficient weather forecasting as well as preparing contingency plans for vulnerable areas. The objectives of this paper are to summarize the available information on adaptation strategies and the mitigation options for climate change to meet the food security in South Asia and Latin America.